Pemanfaatan Media Sosial Dalam Memahami Perilaku Konsumen Terhadap Keputusan Pembelian - Nilna Muna; I Putu Miartana (Universitas Pendidikan Nasional, 2018)
ABSTRACTThis research aims to determine the benefits of social media in understanding consumer behavior toward purchase decisions of Jewelry accessories in MOD-Collection. Social media is one of the media where its participant can interact and share information with other user's. Social media in business has benefits for online branding, marketing, building relationship and word of mouth / networking, where it can use to understand consumer behavior & purchase decision. Consumer behavior & purchase decision in social media can be identified from the needs & desires which shows from their interaction & communication in media social. This research uses qualitative method which involved 8 subject informants. Techniques of data collection is done by observation and deep interview. The results of this study indicate that consumer behavior influenced by culture, social, personal and psychological factors while purchase decision influenced by price, quality, communication convenience and goods design factors.